2015
DOI: 10.3354/dao02810
|View full text |Cite
|
Sign up to set email alerts
|

Batrachochytrium dendrobatidis exposure effects on foraging efficiencies and body size in anuran tadpoles

Abstract: Chytridiomycosis, the amphibian disease caused by the pathogenic fungus Batrachochytrium dendrobatidis (Bd), is fatal to adults of many species. Bd is largely sublethal to amphibian larvae; however, it is known to reduce larval (i.e. tadpole) growth rates, with possible long-term effects on population dynamics and fitness. We conducted an experiment to test how Bd altered southern leopard frog Lithobates sphenocephalus tadpole mouthpart damage, percentage of food ingested, and subsequent body size. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…However, by metamorphosis, the effects of Bd on development were evident, with Bd‐exposed tadpoles metamorphosing sooner than unexposed individuals, even though mass was not affected by Bd exposure. Although qPCR analysis detected infections in only approximately half of the tadpoles exposed to Bd, previous studies have shown that exposure can incur costs, even in the absence of detectable infections (Rohr et al ., ), and that Bd exposure may be a better predictor of effects than Bd load (Hanlon et al ., ). In response to Bd infection, larval amphibians generally delay metamorphosis (Parris & Baud, ; Parris & Cornelius, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, by metamorphosis, the effects of Bd on development were evident, with Bd‐exposed tadpoles metamorphosing sooner than unexposed individuals, even though mass was not affected by Bd exposure. Although qPCR analysis detected infections in only approximately half of the tadpoles exposed to Bd, previous studies have shown that exposure can incur costs, even in the absence of detectable infections (Rohr et al ., ), and that Bd exposure may be a better predictor of effects than Bd load (Hanlon et al ., ). In response to Bd infection, larval amphibians generally delay metamorphosis (Parris & Baud, ; Parris & Cornelius, ).…”
Section: Discussionmentioning
confidence: 99%
“…In anuran larvae, clinical signs of chytridiomycosis due to B. dendrobatidis are generally limited to depigmentation of the mouthparts, without morbidity and mortality [ 3 , 59 ]. However, B. dendrobatidis may cause sub-lethal effects, including lethargy or poor swimming abilities, leading to low foraging efficiencies which is reflected in reduction in body size [ 60 ]. In metamorphosed amphibians clinical signs are variable and range from sudden death without obvious disease to significant skin disorder but infection may nonetheless elapse asymptomatically.…”
Section: The Disease Chytridiomycosismentioning
confidence: 99%
“…hair follicles, glands), or glandular products of the skin (Meteyer et al, 2009;Rosenblum et al, 2010;Martel et al, 2013). These pathogens cause physiological disruption by permeating the skin, which can lead to mortality (Voyles et al, 2009;Cryan et al, 2010;Martel et al, 2013;Warnecke et al, 2013;Verant et al, 2014), but for hosts that do not suffer mortality, there are often latent challenges associated with skin damage, including structural changes to locomotor and sensory organs (Parris and Beaudoin, 2004;Reichard and Kunz, 2009;Venesky et al, 2009;Chatfield et al, 2013;Hanlon et al, 2015), which can influence survival and reproduction after primary pathology has subsided.…”
Section: Introductionmentioning
confidence: 99%